Evaluation of dairy performance of crossbred (Buffalypso x Carabao) buffalo cows - Garc?a, Yenni; Fraga, Luis Mateo; Guzm?n, Gladys; Mora, Martha; Garc?a, Daimy; Padr?n, E. (Cuban Journal of Agricultural Science, 2012)
Dairy performance of crossbred buffalo cows was characterized using 18 412 milk yields on the test-day and accumulated milk yields (2 575, 1 838 and 1 155) at 100, 200 and 244 d of lactation, respectively. Animals belonged to 37 herds of the Crossbreeding enterprise ?El Cangre?. The Mixed procedure of SAS was applied to analyze the fixed effects: calving year (7), calving season (2), herd (37), lactation number (9), test-day order (9) and random effect of each animal living in the herd (1377). Yield means on the test-day was 3.4 kg and adjusted to 244 d of 860.3 kg. The first lactation was of lowest yield, with 2.58 ? 0.03 kg on the test-day and accumulated milk yield at 100, 200 and 244 d: 346.6 ? 5.0 kg, 629.2 ? 12.5 kg and 762.1 ? 19.8 kg. Buffalo cows calving in July-October showed the highest yields: 3.27 ? 0.03 kg, 425.9 ? 4.6 kg, 768.0 ? 11.1 kg and 923.8 ? 16.9 kg, respectively. Accumulated milk yield at 244 d was maintained constant from 2004 to 2009. In the studied population there were productive fluctuations associated to the effects of the number of lactation, test-day order, herd, season and calving year. General means were above to what was reported in Cuba in previous studies. However, a tendency towards a productive rise is not described. Genetic and environmental measurements are required to attain better performance. Key words: buffalo cows, environmental factors, milk